Integration of virtual and real environments for engineering service-oriented manufacturing systems - Leitão, Paulo (2012)
Engineering frameworks are currently required to support the easy, low-cost, modular and integrated development of manufacturing systems addressing the emergent requirements of re-configurability, responsiveness and robustness. This paper discusses the integration of 2D/3D digital software tools with Petri net based service-oriented frameworks to allow the design, configuration, analysis, validation, simulation, monitoring and control of manufacturing systems in a virtual environment and its posterior smooth migration into the real ”physical” environment. An experimental case study was implemented to validate the proposed concepts, using the Continuum platform to design, compose, analyze, validate and simulate the Petri nets based service-oriented manufacturing control system, and the Delmia Automation™ software suite to support the rapid prototyping and the easy simulation of the designed control solution. The experimental results prove several aspects of the proposed approach, notably the smooth migration between the design and the operation phases, one of the main objectives of the work.